EFFECTS OF DIET ON CCL11 EXPRESSION AND AGING OF LUNGS AND TESTES OF MICE - S. Rehman; S. Nadeem; H. Zaman; M. S. Aslam; Z. Abbas (Journal of Animal and Plant Sciences, 2023)
Aging is a complex phenomenon symbolized by dynamic loss of tissue homeostasis with diminished cellular function. Along with genetic factors, many epigenetic factors as such lifestyle of an individual also affects aging. The aim of this study was to check the effect of different food habits in the process of aging using an aging biomarker CCL11. An increase in expression of CCL11 was observed in carbohydrate and fat rich foods groups. However, no effect on CCL11 expression was seen in calorie restricted diet groups. Mice fed with carbohydrates rich food gained weight, showed high levels of glucose, HDL and triglycerides while consumption of fat rich food in mice raised serum levels of anti-nuclear antibodies and LDL comparing to the control groups. Different food habits affected differently the serum levels of glucose, anti-nuclear antibodies, and lipid profile. H and E staining of testis and lungs showed that consumption of fat rich food caused emphysema, epithelial degeneration of lungs and aspermatogenesis in testes. Moreover, Calorie restricted diet showed vacuolization in testis. This study shows that food influence aging, expression levels of CCL11, physiology and morphology of lungs and testes in mice.
Keywords: Aging; CCL11; epigenetic factor; aspermatogenesis; dietary habits